Ground Pressure Control With Use Of Freezing Rocks On The Ore Deposits Of Yakutia - G. P. Neobutov (International Conference on Ground Control in Mining, 1996)
The near surface inclined gold ore deposit is mined out at freezing temperature. The replacement of ore pillars by artificial freezing rocks during the rock pressures control in this conditions presented no difficulties. At the present, the mining operations are maintained at a depth of more than 300 meters. The exploration of mining conditions showed partial warming of rock mass and unstable ground conditions. Analytical calculations using a mathematical model of heat exchange predicted undesirable duration of freezing of artificial pillars. Practical techniques and recommendations for mining with ice pillars as an artificial support system using a new freezing method are discussed.